The Role of Parents in Improving Adaptive Behavior of Children with Mild Intellectual Disabilities in Special Schools - Zerlita, Riri; Qohar, Hendri Abdul (Universitas Pahlawan Tuanku Tambusai, 2025)
This study aims to examine the role of parents in improving adaptive behavior as preparation for work among mildly intellectually disabled students in grade XII at SLB Amalia Bhakti Conggeang. In the context of vocational education, consistent parenting based on positive reinforcement has proven effective in improving the independence and life skills of children with intellectual disabilities. A qualitative approach with case studies was chosen to gain a deeper understanding of the role of parents in supporting their children at home and at school. The research findings indicate that parents who actively engage in daily activities, such as providing opportunities for independent practice and applying positive reinforcement, significantly contribute to the development of adaptive behavior in children. However, challenges faced by parents, such as limited knowledge, time, and resources, hinder the implementation of effective parenting strategies. Therefore, this study recommends the development of parent training programs that can improve their understanding of how to support the development of children with mild intellectual disabilities, as well as strengthen collaboration between parents, educators, and the community. With the right support, children with mild intellectual disabilities can develop the skills necessary to adapt to the world of work.